The Necessity of Medical Humanities Education to General Practitioners: A Brief Review - Wenwen ZHAO; Rongying WANG; Yayi WANG; Min ZHANG; Tianlu YIN (Tehran University of Medical Sciences, 2020)
To the ultimate overall goal to train sufficient numbers of highly qualified general practitioners. We analyzed the recent study on the necessity of medical humanities education for general practitioners and the status of the humanities education of general practitioners. Meanwhile, the model of medical humanities education for general practitioners in China in the future is prospected, with the support of the general practice departments in comprehensive tertiary hospitals. Improving the training mode of general practitioners is performed by a combination of enhancing their clinical skills and medical humanity education, cultivating high-quality general practice faculty by the use of innovative teaching methods. General practitioners need to have a comprehensive understanding of patients and their needs, integrate the whole process of "seeing patients" and "seeing people", consider the best interests of patients, and adopt the most effective treatment plan, which involves human value care and reflects medical humanistic quality. Therefore, general practitioners should have medical humanistic education. The general practice education system in the developed countries in Europe and America is relatively mature, and the medical humanistic quality education of general practitioners is explored early. On the other hand, in mainland China, general practice starts late and develops slowly, and the medical humanistic quality of general practitioners is not sufficiently paid attention to. Currently, there are still many problems to be further addressed and resolved.